2001
DOI: 10.1242/jeb.204.7.1247
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a form of adrenergic response to stress in the mollusc Crassostrea gigas

Abstract: Catecholamines and pro-opiomelanocortin (POMC)-derived peptides, some of the central regulators of the stress-response systems of vertebrates, are also present in invertebrates. However, studies are needed to determine how these hormones participate in the organisation of neuroendocrine stress-response axes in invertebrates. Our present work provides evidence for the presence of an adrenergic stress-response system in the oyster Crassostrea gigas. Noradrenaline and dopamine are released into the circulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…Catecholamine (CA) is one of the hormones to modulate the proximal tubular sodium transport in the mammalian kidney . In oysters, hyposalinity was reported to elicit a significant increase in the expression of two circulating CAs, noradrenaline (NA) and dopamine (DA), whose concentrations peaked at 12 h and lasted up to 72 h of poststress . In contrast, our results showed that hyposalinity could reduce the expression of renalase, which is a secreted amine oxidase to metabolize circulating CAs, indicating that the oyster could reduce the degradation rate of CAs to enhance osmotic stress tolerance.…”
Section: Resultscontrasting
confidence: 58%
“…Catecholamine (CA) is one of the hormones to modulate the proximal tubular sodium transport in the mammalian kidney . In oysters, hyposalinity was reported to elicit a significant increase in the expression of two circulating CAs, noradrenaline (NA) and dopamine (DA), whose concentrations peaked at 12 h and lasted up to 72 h of poststress . In contrast, our results showed that hyposalinity could reduce the expression of renalase, which is a secreted amine oxidase to metabolize circulating CAs, indicating that the oyster could reduce the degradation rate of CAs to enhance osmotic stress tolerance.…”
Section: Resultscontrasting
confidence: 58%
“…Oyster hemocytes have been found to express adrenergic receptors (target receptors for NA), and the effects of NA on oyster hemocyte physiology have been well documented. In fact, hemocytes are known to undergo apoptosis (programmed cell death) upon NA stimulation. Since oysters are a prominent fouling species and their cells express the target receptors, hemocytes make for a good model system to screen NA-conjugated polymer surfaces. , A similar strategy was employed by Gohad et al . to observe interactions between NA-conjugated PHEMA and PMAA polymer brushes and oyster hemocytes .…”
Section: Resultsmentioning
confidence: 99%
“…DA, NE, and E are present in various tissues of mollusks (in particular, bivalves), including the ganglion, hepatopancreas, and hemocytes [ 30 , 57 , 58 , 59 , 60 ]. The source of catecholamines in bivalves is predominantlythe neurosecretory neurons of the central nervous system (CNS) [ 30 , 61 ]; their secretion in hemocytes has also been reported [ 30 , 35 ]. Although DA, NE, and E have been identified in the mollusk CNS [ 30 , 54 ], DA isthe only catecholamine recorded inbivalve ganglia, according to immunohistochemical methods.…”
Section: Biogenic Aminesmentioning
confidence: 99%
“…In the CNS, DA-ergic neurons have been found in Mytilus edulis [ 62 ], Placopecten magellanicus [ 59 , 63 ], and Patinopecten yessoensis [ 64 , 65 ]. A number of experimental studies have shown variations in the CA level in the CNS and hemolymph of mollusks exposed to various stress factors [ 61 , 66 , 67 , 68 ].…”
Section: Biogenic Aminesmentioning
confidence: 99%